Strengthening Youths Skill: Wiring Workshop in Rural Area - Mad Kaidi, Hazilah; Fazilah Mohd Hashim, Nor; Nabil Muhtazaruddin, Mohd; Aini Bani, Nurul; Ahmad, Norulhusna; Mohamed, Norliza; Musa, Rafizah; Salim, Fatimah (International Journal of Engineering and Technology, 2018)
Youth is known as an energetic people with a high potential, and eager to try something new. Therefore, it is such a loss if the abilities that they have been wasted and not fully utilised in a proper way. Project of the electrical wiring workshop is one of the great initiatives as it provides a knowledge base and develops skills in technology and engineering especially in a rural area. In addition, the workshop also aims to develop interpersonal, communication and lifelong learning skills. The ability of youth also increases in generating side income and entrepreneurship nowadays. Through involvement, participants in the wiring workshop have been exposed with a variety of basic installation and wiring techniques whereby they are able to shape their personalities with the advantage of skills in technology and engineering acquired. As a result, return on investment (RoI) can be achieved in the workshop which being conducted at Kampung Pasir Puteh, Kalumpang Hulu Selangor, Malaysia.Â Â Â